THE EFFECTIVENESS OF WORKSHEET WITH CHEMO-ENTREPRENEURSHIP ORIENTED ON COLLOID MATTER TO TRAIN CREATIVE THINKING SKILL - Dwi Yuni Hartini; Utiya Azizah (JPPS (Jurnal Penelitian Pendidikan Sains), 2019)
The aim of this research is to describe the effectiveness of student worksheet with Chemo-Entrepreneurship oriented on colloid matter to train creative thinking skill. This research use Research and Development design with one group pretest and posttest method in 12th grade of SMAN 1 Driyorejo Gresik to know the effectiveness of worksheet. The instrument used in this research was creative thinking skill test sheet. The worksheet stated effective if the posttest result for each component of creative thinking get percentage >75% with creative thinking ability in high or very high category. The result of research shown that there was an increase in students creative thinking skill abilities. The pretest result shoen that the students creative thinking skill ability were in low and very low category, while the posttest result of creative thinking skills shown that students creative thinking skills were in the high and very high category with each component of creative thinking such as fluency, flexibility, elaboration and originality thinking got percentage  91,67%, 85,97%, 77,8%, 81,25%.